Production of monoclonal antibodies to Legionella pneumophila serogroups 1 and 6. - Para, M F (1983)
To better define the surface antigens of Legionella pneumophila for clinical and experimental purposes, we have produced monoclonal antibodies to L. pneumophila serogroups 1 and 6. Two hybridomas were produced in serogroup 1. One antibody, LP-I-17, recognized a serogroup-common antigen. The second antibody, LP-I-81, was specific for serogroup 1. This antibody was able to agglutinate bacterial cells belonging to the serogroup 1 reference strains. Philadelphia and Knoxville. Microagglutination assays of environmental and clinical isolates revealed a subgroup of serogroup 1 environmental isolates which were not agglutinated by LP-I-81. This subset of isolates was segregated to certain buildings in the medical complex. Immunodiffusion studies showed identity between the LP-I-81 antigen and the serogroup-specific antigen of serogroup 1 organisms. This antigen could be absorbed out of the serogroup 1 organism extract with LP-I-81-coated Staphylococcus aureus, leaving the serogroup-common antigens. Three hybridomas were produced to serogroup 6. All three produced antibodies which were serogroup 6 specific and agglutinated serogroup 6 bacteria.